Observer‐based fixed‐time task‐space cooperative tracking control of networked Lagrangian agents with quantized communication - Ding, Teng‐Fei; Zhang, Qiu‐Yue; Ge, Ming‐Feng; Liu, Jie; Park, Ju H. (International journal of robust and nonlinear control, 2024)
In this article, the task‐space cooperative tracking control (TSCTC) problem of networked Lagrangian agents (NLAs) with quantized communication is investigated in fixed time, where every Lagrangian agent suffers from imprecise dynamics and external disturbances. A hierarchical observer‐based fixed‐time control (HOBFTC) algorithm is proposed, where there are four parts: a prescribed‐time input observer is proposed to recover the unknown input of the leader, a distributed estimator control is designed to force the estimated values to converge the states (position and velocity) of the leader, a fixed‐time disturbance observer is presented to recover the total disturbances of NLAs, and a nonsingular fixed‐time local control is given to guarantee that the task‐space cooperative tracking can be achieved. The salient features are twofold: (1) by employing the hierarchical control strategy, the proposed control algorithm is clearly structured to solve the complex cooperative tracking problem with multiple constraints including quantized communication, imprecise dynamics and external disturbances. (2) the convergence time of the proposed control algorithm can be set freely by selecting some parameters, which are independent of the initial conditions. Some sufficient conditions are obtained and some simulation examples are given to validate the effectiveness of the proposed algorithm.